Optimizing the Role of Regional Governments in Controlling Pollution and Environmental Damage Following the Enactment of the Job Creation Law - Pangestu, Ilham Aji; Nadian Syah, Alfiah (Jurnal Geuthèë: Penelitian Multidisiplin, 2025)
This study aims to analyze changes in regional government authority in controlling pollution and environmental damage following the enactment of the Job Creation Law and to formulate strategies to strengthen regional roles to maintain effective environmental protection. This research is a normative legal study with a descriptive-analytical nature. The legal materials in this study include secondary and primary legal materials obtained through literature review. The approach used is the legislative approach. The results show that the centralization of licensing through the OSS-RBA and a risk-based approach have reduced regional authority in issuing environmental permits, while regional governments remain burdened with the responsibility for supervision and initial action. This condition creates an imbalance of authority, legal uncertainty and weakens the effectiveness of pollution prevention. This study recommends first, the central government must ensure openness and integration of access to licensing information for regions; second, revise and harmonize implementing regulations governing the division of central and regional authority in the environmental sector; third, strengthen the authority of regional governments for administrative sanctions; and fourth, establish a joint governance model between the central and regional governments based on equal coordination and a clear division of tasks. Fifth, increase the human resource capacity of environmental supervisors in the regions and provide adequate monitoring infrastructure.